2014
DOI: 10.1371/journal.pone.0096649
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselectivity of Isoflurane in Adhesion Molecule Leukocyte Function-Associated Antigen-1

Abstract: BackgroundIsoflurane in clinical use is a racemate of S- and R-isoflurane. Previous studies have demonstrated that the effects of S-isoflurane on relevant anesthetic targets might be modestly stronger (less than 2-fold) than R-isoflurane. The X-ray crystallographic structure of the immunological target, leukocyte function-associated antigen-1 (LFA-1) with racemic isoflurane suggested that only S-isoflurane bound specifically to this protein. If so, the use of specific isoflurane enantiomers may have advantage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Ultimately, the precise mechanism might be difficult to determine because propofol, like many general anaesthetics, is a promiscuous drug, having hundreds of molecular targets. 39 Potential targets mediating a protective effect could include several mitochondrial proteins, leucocyte integrins, 40 and sirtuin deacetylases. 41 The mortality associated with the present study is higher than observed in the clinical application of propofol for surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, the precise mechanism might be difficult to determine because propofol, like many general anaesthetics, is a promiscuous drug, having hundreds of molecular targets. 39 Potential targets mediating a protective effect could include several mitochondrial proteins, leucocyte integrins, 40 and sirtuin deacetylases. 41 The mortality associated with the present study is higher than observed in the clinical application of propofol for surgery.…”
Section: Discussionmentioning
confidence: 99%
“…A number of direct anesthetic targets on immune cells have been reported. These targets include adhesion molecules integrins [79][80][81][82][83][84], TLRs [85][86][87], and intracellular molecule Rap1 [76]. Volatile anesthetic integrin targets include leukocyte-function associated antigen-1 (LFA-1) and macrophage-1 antigen (Mac-1), both of which are expressed on neutrophils.…”
Section: The Effect Of Anesthetics On Neutrophil Functions Andmentioning
confidence: 99%
“…This approach has verified a large number of plausible targets, including, but not limited to: specific ligand-gated ion channels [147,148], voltage-gated channels [149,150], hyperpolarizationactivated cyclic nucleotide (HCN)-gated and tandem pore potassium (K 2 P) channels [151], and mitochondrial proteins [152]. Attempts to distinguish functional significance of these many targets has used sensitivity, stereoselectivity [153], alkanol cutoff effect [9,154], and other phenomenological observations, some of which has caused further ambiguity. Nevertheless, this has been a powerful approach that has constrained the degree of potential complexity.…”
mentioning
confidence: 99%